Ashen Hearts and Astral Zones: Bashevis Singer in Yiddish and English Preparations - Waldinger, Albert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2002)
AbstractThis article interprets the career of the Yiddish writer Isaac Bashevis Singer, winner of the Nobel Prize for Literature in 1978, in English translation. Involved is an understanding of the emotional and linguistic impact of the Haskala or “Jewish Enlightenment” on Polish Jewisk life as well as of the other ideologies confronting Jewry—Socialism, Zionism and Hassidic Return, for example. Involved also is a just evaluation of the linguistic achievements of Singer’s translators, especially Jacob Sloan, Cecil Hemley, Elaine Gottlieb, Saul Bellow and Isaac Rosenfeld, all of whom have a creative identity with a thematic and stylistic influence on translation quality. An attempt is likewise made to demonstrate Singer’s transcendence of his rabbinical past and of his refuge in the United States.